The Effect of Audit Opinion, Financial Distress, Client Size, Management Turn and KAP Size on Auditor Switching - Novi Darmayanti (Universitas Hayam Wuruk Perbanas, 2017)
The issue of Auditor Independence, the most frequently, makes the debate of auditor rotation. This auditor rotation is related to the company activity for doing auditor switching. Some previous studies showed that switching auditors leads to the various result and it needs to hold rediscovery and to verify the theory of auditor switching. The study Aimed to test empirically the auditor opinion, financial distress, the client company size, management turnover, and KAP size toward auditor switching on manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2010 until 2014. The study is an explanatory quantitative research with purposive sampling technique for the collection of data. The 39 manufacturing companies used as a sample. The study used SPSS Application with 18 version and regression logistics to test the hypothesis because the independent variable is the combination between metric and non-metric. The result of the study Showed that the independent variable has an effect on auditor switching and auditor’s opinion. Financial distress, the client company size, management turnover and the firm size do not affect the auditor switching.